(untitled) (Scientific journal of the Fergana State University, 2024)
Higher education plays an important role in the development of society in acquiring the knowledge and skills necessary for students to achieve success in the professional field and active participation in social life. It helps the intellectual and cultural development of a person, as well as the creation of new knowledge and technologies. The world’s leading countries, such as Germany, are paying special attention to education, spending money on it, developing advanced curricula and teaching methods. Germany is known for its high-quality education system, and higher education in the country has a long history. German universities lead the way with high levels of research and teaching, as well as innovative approaches to education. Germany is a favorable country for students who want to get quality education and expand their knowledge in various fields. It is dedicated to the comparative study of lexical units related to the higher education system in Germany and Uzbekistan. First, let’s look at the characteristics of German universities, as well as concepts related to the educational process and the organization of higher education in this country. In the German education system, it is important to understand what opportunities are provided for students, the choice of curricula and teachers, as well as the knowledge assessment system. Based on this analysis, it is possible to better understand the importance of higher education in the social development of Germany and the contribution of this country to the development of the field of education on a global scale.